دور الترويج الإلكتروني في تنمية ولاء الزبون -دراسة ميدانية على عينة من زبائن مؤسسة موبيليس - بوزوايد إكرام; قلومة نور الهدى; قلومة آسيا فريحة (جامعة عمار ثليجي الاغواط, 2022)
The aim of this study is to know the role of electronic promotion in the development of customer loyalty from the viewpoint of the latter, and thus to identify the elements of the electronic promotional mix represented in electronic advertising, electronic public relations and electronic sales activation and its impact on the affiliation of customer loyalty in response to these electronic means and from In order to understand the aspects of this study, we used the questionnaire as a tool for collecting primary data, which was directed to a sample of the study community represented by the users of the Mobilis phone dealer in the state of Laghouat. Several results were reached, the most important of which are, that there is a statistically significant relationship in the role of the electronic promotional mix on the development of customer loyalty, It also appeared to us that electronic advertising in its various forms is one of the most influential elements of electronic promotion on the development of customer loyalty, then electronic public relations, and finally the activation of electronic sales. Loyalty is the customer’s behavior in repeating the purchase of the same product or service or the same brand, that is, he gives preference in his dealings to a particular brand or product without dealing with competitors, despite the competitors’ marketing efforts and attempts to change his decision. Loyalty behavior is evident by studying the relationship (customer/seller). In the beginning, the customer is a potential customer, he can make the purchase or he may not, and the institution is trying to encourage this customer to make the first purchase to become a new customer, and it continues to encourage him to repurchase several times to become between him and him. The institution is a relationship characterized by loyalty, so he becomes not only buying, but also a process of publicizing the institution by spreading his positive experiences, thus urging the individuals around him to buy as well.